Development of Interests and Talents to Increase the Creativity of UPT SPF Students at SMP Negeri 48 Makassar - Ahmad Fajri Shafwan; Sahra Mawarda Aziz; Dita Anggraeni; Hijriana; Muh. Samhi Muawwan AM (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the abilities and talents of students through the development of interests and talents carried out at UPT SPF SMP Negeri 48 Makassar. This research uses a qualitative approach with a descriptive qualitative research type. Data collection through observation, distribution of questionnaires and documentation. The data analysis technique used in this research is qualitative analysis by analyzing, describing, illustrating and deciphering various events that occurred during the research and also information obtained from questionnaires that have been filled in from informants. The research results show; 1) The development of interests and talents of students which was carried out at UPT SPF SMP Negeri 48 Makassar, received a good response from the school and also students; 2) The progress produced during this interest and talent development training activity is 80% which proves that UPT SPF students at SMP Negeri 48 Makassar have extraordinary interests and talents; 3) Some important points that need to be considered in developing the interests and talents of students, especially at UPT SPF SMP Negeri 48 Makassar, namely attention, collaboration between parents and teachers, learning and training, providing motivation and reinforcement, and extracurricular activities.